A study of contingency relationships between supplier involvement, absorptive capacity and agile product innovation. Issue 1 (2014) - ,; ,; ,
<x xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to employ agility concept to develop a contingency perspective of relationship between suppliers' involvement, absorptive capacity (AC) and product innovation ( PI ). While the moderating effect of AC on the relationship between supplier involvement and PI performance is investigated, a firm's agility in PI is entered as one dimension of the firm's performance to accommodate a multidimensional perspective. Design/methodology/approach – The paper formulates six hypotheses extracted from the relevant literature. The survey was conducted over the internet by using web‐based questionnaire. A sampling frame of 1, 200 manufacturing UK‐based companies provided 233 usable responses. A confirmatory factor analysis was used to test a validity and reliability of constructs and further the paper employed hierarchical multiple regression to test the research hypotheses. Findings – The results while reaffirm some of the existing theories of the subject provide some differing view of the issues allowing projection of new insight on the approach to PI and involvement of suppliers. The results support the proposition of PI performance multidimensionality where achievements beyond financial and market‐related factors play a critical role. Furthermore, research findings suggest AC as a competitive factor that can provide the grounds for proactively winning in the PI game through increasing agility capabilities. Research limitations/implications – This study uses a random sample of UK manufacturing companies, which could be extended to firms from outside the UK too. Originality/value – The paper provides a new insight into the existing literature on "new product innovation" and its relationship with suppliers' involvement as well as the firm's AC by employing agility perspective, as a leading theory to explain dynamics and uncertainties in the business environment.